Numerical simulation of fluid mud layer in estuaries and coastal areas - Chung, Dang Huu (Vietnam Journal of Mechanics, 1998)
In this paper the formation and development of fluid mud layer happening in estuaries and coastal areas are studied in detail through numerical simulation on the basis of the 2D shallow water equations for tidal flow, the advection-diffusion equation for cohesive sediment transport and the equations for fluid mud transport. Numerical solution of a special case for a part of the Severn estuary is obtained using the finite difference method as an illustration of the applicability of the model in practice. On the basis of the results, initial remarks and evaluation are given.